VD_FINDINFO HC / 2025 / 230 vom 17. April 2025 - VD Tribunal cantonal (2025)
RÉSERVE DE L'ORDRE PUBLIC, OBLIGATION D'ENTRETIEN, BIGAMIE | 105 ch.1 CC, 176 al. 1 ch. 1 CC, 176 al. 1 ch. 3 CC, 285 al. 1 CC